Gastric Ulcer Healing Effect of Bangle (Zingiber cassumunar (Roxb.)) Rhizome Extract in Aspirin-induced Rats Model - Yuniarto, Ari; Susilawati, Elis; Rahman, Toni Abdul; Setiawan, Finna; Juanda, Dadang (Indonesian Journal of Pharmaceutical Science and Technology, 2017)
In the gastrointestinal system, gastric ulcers are one of the common serious diseases. The pathophysiology of gastric ulcer is an imbalance between aggressive and mucosal defense factor. Imbalance between aggressive and mucosal defense factor have contribution against developed of gastric ulcer disease. The objective of the research was to evaluate gastric ulcer healing effect of Bangle (Zingiber cassumunar (Roxb.) rhizome extract in aspirin-induced rats model. Antiulcer activity of Bangle rhizome extract was evaluated by several parameters involving gastric acidity, number of ulcers, diameters of ulcers, ulcer index, and healing ratio. Doses level of Bangle rhizome extract which used in this study such as 50 mg/kg and 100 mg/kg, respectively. Histopathological of the stomach was performed using hematoxylin-eosin stained. The results of study showed that groups which given Bangle rhizome extract have signi cant effect in gastric acidity, number of ulcers, diameters of ulcers, ulcer index, and healing ratio compared to the control group. Histopathological study of the stomach ulcers showed tissues regeneration in group were treated by Bangle rhizome extract compared to the control group. It can be concluded that from the experimental study of Bangle (Zingiber cassumunar (Roxb.)) rhizome extract have potential antiulcer activity in aspirin-induced rats model. KeywordsÂ : Zingiber cassumunar (Roxb.), Extract, Ulcer, Aspirin.Â